2018
DOI: 10.1093/geronb/gby119
|View full text |Cite
|
Sign up to set email alerts
|

Is Living Alone “Aging Alone”? Solitary Living, Network Types, and Well-Being

Abstract: Objectives When identifying older adults who may be at risk of being without necessary supports, policy makers and scholars tend to focus on those living alone, neglecting differences within that group. We examine how their social networks contribute to subjective well-being, why some of them fare better and compare their well-being to older adults coresiding with others. Method Data are from the fourth wave of the Survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
109
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 59 publications
10
109
1
1
Order By: Relevance
“…Five distinct network types emerged from the latent class analyses. The restricted 'no confidants' type is associated with loneliness in this study, and moreover has likeness to the 'detached' type found by Karpinska and Dykstra (2018), and it is similar to the 'restricted' types found in other studies where Poles were also included (Djundeva, Dykstra, and Fokkema 2018;Litwin and Stoeckel 2013). The typical 'diverse' social network type (similar to the diverse type in Fiori, Smith, and Antonucci 2007) in this study was characterised by a large non-homogeneous network with kin and non-kin support, and somewhat less by transnational ties.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Five distinct network types emerged from the latent class analyses. The restricted 'no confidants' type is associated with loneliness in this study, and moreover has likeness to the 'detached' type found by Karpinska and Dykstra (2018), and it is similar to the 'restricted' types found in other studies where Poles were also included (Djundeva, Dykstra, and Fokkema 2018;Litwin and Stoeckel 2013). The typical 'diverse' social network type (similar to the diverse type in Fiori, Smith, and Antonucci 2007) in this study was characterised by a large non-homogeneous network with kin and non-kin support, and somewhat less by transnational ties.…”
Section: Discussionsupporting
confidence: 87%
“…In doing so, we built on previous network type studies that have used only size, and friend vs. family distinctions. 'Diverse', 'family-focused', 'friend-focused', and 'restricted' network types have previously been discussed in the non-migration oriented literature (Djundeva, Dykstra, and Fokkema 2018;Litwin and Shiovitz-Ezra 2010) but to our knowledge this is among the first studies to employ social network types investigating migrant support networks. Next to dimensions identified in previous research (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential explanation for these Table 4 Main effects and interactions of living arrangements and fracture state (the first post-fracture year) on the mortality risk stratified by sex mixed findings is that old people who live alone do not form a uniform group but consist of both socially isolated and socially integrated persons. In fact, in many modern societies older adults who live alone often have large and diverse social networks [35]. Therefore, living alone does not necessarily indicate social isolation and/or loneliness, both of which are important psychosocial mechanisms influencing health [1].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined concepts similar to happiness, including well-being [7], quality of life [9,12,13,14], life satisfaction [6,15,16], subjective well-being [17], good life, and better life [5,18].…”
Section: Introductionmentioning
confidence: 99%